-8v+12=-4(v-9)

Simple and best practice solution for -8v+12=-4(v-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8v+12=-4(v-9) equation:


Simplifying
-8v + 12 = -4(v + -9)

Reorder the terms:
12 + -8v = -4(v + -9)

Reorder the terms:
12 + -8v = -4(-9 + v)
12 + -8v = (-9 * -4 + v * -4)
12 + -8v = (36 + -4v)

Solving
12 + -8v = 36 + -4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '4v' to each side of the equation.
12 + -8v + 4v = 36 + -4v + 4v

Combine like terms: -8v + 4v = -4v
12 + -4v = 36 + -4v + 4v

Combine like terms: -4v + 4v = 0
12 + -4v = 36 + 0
12 + -4v = 36

Add '-12' to each side of the equation.
12 + -12 + -4v = 36 + -12

Combine like terms: 12 + -12 = 0
0 + -4v = 36 + -12
-4v = 36 + -12

Combine like terms: 36 + -12 = 24
-4v = 24

Divide each side by '-4'.
v = -6

Simplifying
v = -6

See similar equations:

| 2x=10(15-3x) | | 3(1)-2y=-6 | | 2(1-e)=3e-8 | | -5(u-3)=-2u-3 | | 2.5*ln(x)-ln(2x)=0 | | 7n+5n=-12 | | 3/8w=5 | | 5w+4-9w-3= | | -6x=3y-1 | | 4x^6+9x^2-2=0 | | Cosx+senx=0 | | w=8+2.5T | | 3w+2=5(w+2) | | X/9=-52 | | (9x)/(7-6x)=15 | | -5(w-6)=-2w+24 | | 5+3*5-1=19 | | 5*x1/2=4 | | 511/2-223 | | 12-4m=6-3m | | 14/5=2x | | 8(0)+2y=-4 | | 4x=6(4.8) | | 11a+9b-2c= | | 8(1)+2y=-4 | | 9•1/3= | | 4y+25=-7(y+9) | | 12=2/5u | | 1.5x+8.4=2.5x | | 3.14/92.8 | | 0.16x=16+0.12x | | -3v+2=-10v-30 |

Equations solver categories